Aflibercept monotherapy or bevacizumab first for diabetic macular edema - Avner Hostovsky; Iris Moroz; Gabriel Katz (Indian Journal of Ophthalmology, 2024)
Purpose: Clinical outcome and switch patterns with bevacizumab first treatment strategy for patients with newly diagnosed neovascular age-related macular degeneration (nAMD). Methods: Retrospective observational study of the number of intravitreal injections of bevacizumab and treatment switch in patients who started intravitreal bevacizumab injections between January 1, 2016 and December 30, 2018. Results: From January 1 2016 to December 31 2018, 608 eyes of 565 patients started intravitreal injections of bevacizumab for a new diagnosis of nAMD. Average visual acuity (VA) at presentation was 0.60 logarithm of the minimum angle of resolution (logMAR), which improved to 0.47 after six injections (P < 0.001) and decreased to 0.63 at the last follow-up (P = 0.543). Switch of treatment was recommended for 190 eyes (31.3%), and of them, 91 patients (15%) were switched during the first 6 months and defined as primary failure of bevacizumab. The switch of treatment resulted in a statistically significant improvement in VA in the first 6 months after the switch. The gain in VA was not sustainable over time. Conclusion: Bevacizumab first treatment strategy produced results that were comparable to previous real-world outcomes publications of ranibizumab and aflibercept treatment with low rates of failure of bevacizumab treatment. Treatment switch to second-line treatment yielded a significant VA improvement, mainly in patients with primary bevacizumab failure.